1989
DOI: 10.1016/0147-9571(89)90062-3
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme-linked immunosorbent assay using canine coronavirus-infected CRFK cells as antigen for detection of anti-coronavirus antibody in cat

Abstract: From the reasons that canine coronavirus (CCV) grows more efficiently than feline coronavirus in a cell culture and they are mutually related in their antigenicities, an enzyme-linked immunosorbent assay (ELISA) using CCV-infected feline kidney (CRFK) cells as substrate antigens was developed for detection of anti-coronavirus antibodies in cats. It was indispensable for generating coronavirus-specific ELISA antibody activities that the sample was applied to the mock-infected, normal CRFK cells in parallel with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Although serological testing by immunofluorescence assay (IFA) (Moestl, 1983) or ELISA (Mochizuki and Furukawa, 1989) is a helpful tool for FIP diagnosis, results can only be interpreted in correlation with clinical symptoms (Sparkes et al, 1991). At present, the only conclusive FIP diagnosis can be established by histopathological examination of a biopsy or post mortem material.…”
Section: Introductionmentioning
confidence: 99%
“…Although serological testing by immunofluorescence assay (IFA) (Moestl, 1983) or ELISA (Mochizuki and Furukawa, 1989) is a helpful tool for FIP diagnosis, results can only be interpreted in correlation with clinical symptoms (Sparkes et al, 1991). At present, the only conclusive FIP diagnosis can be established by histopathological examination of a biopsy or post mortem material.…”
Section: Introductionmentioning
confidence: 99%
“…The TGE virus and other porcine coronaviruses, as well as CCV are antigenically related to FECV/FIPV. The antigenic relationships amongst the coronaviruses affecting pigs, cats and dogs was recognized prior to the actual isolation of feline coronaviruses in cell culture, and has since been expanded to isolates propagated in vitro (Horzinek, et al 1982;Mochizuiki and Furukawa, 1989;Pedersen et al, 1978;Sanchez et al, 1990). In addition to the serologic cross reactions among this coronavirus group, there have been molecular studies reported on the homology of the viral RNA (DeGroot et al, 1988;Shockley et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The antigenic and genomic similarities amongst the porcine, canine and feline coronaviruses have led to speculation on the common origins of the coronaviruses (Barlough and Stoddart, 1990;Yaling, et al, 1988 ). The potential for interspecies transmission of these coronaviruses whenever these animal species commingle needs to be studied further (McArdle, et al, 1990;Mochizuiki and Furukawa, 1989;Sanchez, et al, 1990;Yaling, et al, 1988 ). The severity of FECV infection is age-related, with clinical signs most frequently being observed in kittens (Pedersen, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Anpep is a receptor commonly used by feline infectious peritonitis virus, transmissible gastroenteritis virus, and infectious bronchitis virus. These viruses have been detected in kidney of cats 53 , 54 . Consistently, Anpep was found to be highly expressed in stromal cells and proximal tubule cells of kidney.…”
Section: Resultsmentioning
confidence: 99%